2009
DOI: 10.2217/rme.09.74
|View full text |Cite
|
Sign up to set email alerts
|

Stem Cell Paracrine Actions and Tissue Regeneration

Abstract: Stem cells have emerged as a key element of regenerative medicine therapies due to their inherent ability to differentiate into a variety of cell phenotypes, thereby providing numerous potential cell therapies to treat an array of degenerative diseases and traumatic injuries. A recent paradigm shift has emerged suggesting that the beneficial effects of stem cells may not be restricted to cell restoration alone, but also due to their transient paracrine actions. Stem cells can secrete potent combinations of tro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
591
1
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 739 publications
(606 citation statements)
references
References 226 publications
(202 reference statements)
10
591
1
4
Order By: Relevance
“…[30][31][32] Therefore, key secretory proteins of human MSCs are also used directly as novel treatments for patients and could be potent biomarkers for selection of superior human MSCs during large-scale cultivation of clinical grade human MSC in Good Manufacturing Practice facilities. 33 Based on these findings, we aimed to determine if either human MSCs or a selection of key secreted proteins may be applicable as novel treatments.…”
Section: Discussionmentioning
confidence: 99%
“…[30][31][32] Therefore, key secretory proteins of human MSCs are also used directly as novel treatments for patients and could be potent biomarkers for selection of superior human MSCs during large-scale cultivation of clinical grade human MSC in Good Manufacturing Practice facilities. 33 Based on these findings, we aimed to determine if either human MSCs or a selection of key secreted proteins may be applicable as novel treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Up to now, a series of research work has demonstrated positive effects of cell therapy on reduction of cardiomyocyte necrosis, induction of angiogenesis and activation of host stem cell recruitment via the secretion of paracrine factors [43]. The clinical benefit of intramyocardial injection of autologous MSCs has also been increasingly reported [5].…”
Section: Discussionmentioning
confidence: 99%
“…3,4 To provide relevant platforms for evaluating regenerative medicine therapies, such in vitro systems should mimic niche environments of a three-dimensional (3D) tissue as closely as possible by allowing for dynamic cell-cell interactions, given that cellular responses can vary substantially depending on the surrounding microenvironment. 5,6 Toward this end, use of biomaterials may provide a way to recreate these 3D environments, while allowing the study of complex cellular interactions. This includes the application of methods for high-throughput, multivariate analyses of highcontent data (e.g., from gene microarrays, suspension arrays, time-of-flight-mass spectrometry, and microscopy images) [7][8][9][10][11] that yield system-level information of complex cellular processes at or close to a single-cell level.…”
Section: Introductionmentioning
confidence: 99%